Protecting the historic buildings of Mexico: the barrel vault of San Agustin Church in Morelia - Alejo, Leslie E. (2021)
Heritage in Mexico is endangered due to exposure to major hazard events and lack of maintenance. The level of knowledge necessary to evaluate structural behavior of historic buildings is generally low, mainly regarding the parameters such as mechanical properties. San Agustin church is one of the most important historical buildings in Morelia City, Mexico. Thus, a comprehensive analysis of the San Agustin church was performed, including a damage survey and dynamic identification tests. Based on the diagnosis, a 3D finite element model with solid elements was developed and calibrated. Then, a seismic assessment was carried out using pushover analysis. The findings about the damage obtained from the numerical analysis is consistent with the actual condition of the church. Finally, a partial model was developed to evaluate the performance of the nave barrel vault strengthened with an extrados masonry arch and a layer of carbon fabricreinforced cementitious matrix, an intervention that substantially increased the horizontal load capacity.